Vascular findings on FDG PET/CT - Liddy, Stephen (Br J Radiol, 2020)
Since its introduction into clinical practice, 2-deoxy-2-[(18)F]flu-D-glucose (FDG) positron emission tomography/computed tomography (PET/CT) has become firmly established in the field of oncological imaging, with a growing body of evidence demonstrating its use in infectious and inflammatory vascular pathologies. This pictorial review illustrates the utility of FDG PET/CT as a diagnostic tool in the investigation of vascular disease and highlights some of the more common incidental vascular findings that PET reporters may encounter on standard oncology FDG PET/CTs, including atherosclerosis, large vessel vasculitis, complications of vascular grafts, infectious aortitis and acute aortic syndromes.